Implementasi Pembelajaran Akidah Akhlak Dalam Mewujudkan Visi Sekolah Di Sekolah Menengah Pertama(SMP) Muhammadiyah 2 Surakarta Tahun Akademik 2015/2016 - Alfu'ah, Anggar; , Dra. Arief Wibowo, M.Ag (2017)
Learning implementation of moral theology in realizing the vision of school is one important element that should be applied at all levels of school, so the learning problems of students are able to overcome. Meanwhile, there are several schools, especially Islamic Integrated Schools believing that teaching moral theology is part of tealizing the vision of schools so they no longer just focus on scoring but also intelligent beings who are responsible for the formation of a noble character of learners. Similarly, the SMP Muhammadiyah 2 Surakarta apply learning in accordance with the school's vision. Therefore, in focus of SMP Muhammadiyah 2 Surakarta, it is conducted a study on "moral theology learning implementation in realizing the vision of the in school academic year 2015/2016. This research is a field research with descriptive qualitative approach through data reduction, data presentation, and conclusion drawing, methods of interview, observations, and documentation in collecting data, and inductive method in analysing data. The results of this study indicate that: (1) implementation of learning moral theology in realizing the vision of the school is applied as good as possible through the concept of classroom teaching and learning with methods that exist; (2) through learning the moral theology learners can improve the spiritual values that correspond to the vision of school; (3) teaching moral theology with the aim to achieve the school's vision so that learners can be pious, humane, cultured and virtuousmen. While the obstacles encountered by teachers of moral theology which is a technical constrain, that is, lack of time in learning, and other constrains from both teachers and students. Teachers are still overwhelmed in the learning process and students still remain being passive during the learning takes place.